Situation Report: Hungary, 28 July 1970 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Party Guidelines on the Preparation of the Fourth Five-Year Plan Oil: A Long-Term Problem First Issue of the Consumer Research Journal Nagyito Franco-Hungarian Economic Co-operation: The Social Effect Youth Travel Problems Further Diplomatic Changes The Use of Indirect Regulators in Agriculture Hard Currency Credits for the Purchase of Agricultural Machinery and Equipment from the West